Teledentistry: Increasing utilisation of oral-health services for children in rural areas. (January 2023) - Surdu, Simona; Langelier, Margaret
Introduction: The objective of this study was to evaluate factors influencing utilisation of follow-up oral-health services in general dentistry clinics among children subsequent to a teledentistry consultation and treatment with a paediatric dental specialist. Methods: Conducted in 2017, the study included 144 children living in rural upstate New York who experienced a teledentistry consultation in 2015–2016 at one of several local general dentistry clinics. A remotely located paediatric dental specialist provided consultation services in the teledentistry visit and treatment services in the specialty dental clinic. Associations between follow-up services at the general dentistry clinics and patients' characteristics, specialty treatment recommendations, case-management services, timeliness of treatments and travel distances were evaluated. Results: The study results indicated that most children completed a treatment plan (97.2%) at the specialty clinic and subsequently accessed follow-up oral-health services at one of the local general dentistry clinics (77.1%) where teledentistry services were provided. Children's utilisation of follow-up services in general dentistry clinics was associated with a shorter time to specialty treatment ( p = 0.013) and fewer case-management contacts ( p = 0.004). Children who had a longer time to treatment initiation ( p < 0.001) or completion ( p = 0.043) required significantly more case-management services than other children. Discussion: The study found that case severity and compliance with treatment were predictors of utilisation of oral-health services in general dentistry clinics. An additional finding was that case-management interventions were important in facilitating specialty dental care.